Понятие и содержание термина «безопасность» - Кулиев, И.О. оглу; Муршудова, С.Х. кызы (Інститут держави і права ім. В.М. Корецького НАН України, 2009)
The article covers the concept of safety, transport safety, aviation safety. There is a comparsion of the Azerbaijan Republic and the Russian Federation in the article.